SHRINE "KHOJAI SAROB OTA". - Kenjayev Abdullaziz Erkin oglu (Western European Studies, 2024)
Jizzakh region, along with many regions of Uzbekistan, has been home to many scholars and historical sites. These monuments serve to reach us very important information from the distant past. At the moment, it is our priority to bring this place to the next generation by drawing public attention to it.
Keywords: Jizzakh monuments; mausoleum; plantain